Six plays of the Israeli-Palestinian Conflict - Khoury, Jamil, 1965-; Najjar, Michael Malek, 1972-; Pond, Corey, 1987- (McFarland & Company, Inc., Publishers, 2018)
"A bold and singular collection of six plays by Arab and Jewish playwrights explores the human toll of the Israeli-Palestinian conflict: The Admission by Motti Lerner, Scenes From 70* Years by Hannah Khalil, Tennis in Nablus by Ismail Khalidi, Urge for Going by Mona Mansour, The Victims by Ken Kaissar, and The Zionists by Zohar Tirosh-Polk"--